Remix and life hack in hip hop : towards a critical pedagogy of music - MacDonald, Michael B., 1974- (Youth, media, & culture series ;, 2016)
Many hiphoppas labour to sustain Hiphop Kulture in their communities far from the big stages, world tours, and hit singles enjoyed by a shockingly few American hiphoppas. The creative labour of these few mega stars is calculated in billions of dollars. But for most hiphoppas, their creative labour may never get expressed in economic terms. Instead it is expressed in social capital, the production of collective and individual subjectivities, the bonds of love that build and hold communities together, and the healing of broken hearts, broken homes, and broken neighborhoods in broken cities. Hiphop Kulture is not a music genre, it is much more, and exploring how the sharing of aesthetic resources builds community, and how situated learning plays a necessary role in cultural sustainability draws out questions that may lead to a model of community located cultural education, and a starting point for a critical pedagogy of music [Publisher description].